(untitled) (International Current Pharmaceutical Journal, 2014)
To assess the adherence of physicians involved in the management of diabetes mellitus with or without co-morbidities with reference to Clinical Practice Guideline 2009 given by Ministry of Health Malaysia in the tertiary care hospital, Pinang General Hospital Malaysia. Cross-sectional study was done at tertiary care hospital, Penang, Malaysia. The total 51 physicians and 1020 patients prescriptions written by same physicians were taken from the record of the Penang General Hospital (20 prescriptions for each enrolled physician). All 1020 patients were suffering from diabetes mellitus with or without co-morbidities. These patients were recruited from the different wards of the Penang General Hospital. Depending on the recommendations of CPG 2009 the prescriptions of patients were divided into adherent and non-adherent prescriptions. The overall good level of physician adherence was seen with respect to the recommendations of CPG 2009 in all prescriptions. A statistically significant negative association (?= 0.094, p-value=0.003) was observed between diabetes mellitus control and co-morbidities. CPG adherent had statistically weak negative association (?= -0.081, p-value=0.010) with patients having co-morbidities. No statistically significant association was observed between CPG adherence and any other co-morbidity. The study explored the several features of prescription pattern of physicians involved in the management of diabetes mellitus with or without co-morbidities and recognized the need for improvement in their prescription pattern for treating the diabetes mellitus. DOI: http://dx.doi.org/10.3329/icpj.v3i8.19405 International Current Pharmaceutical Journal, July 2014, 3(8): 309-312